2023
DOI: 10.3390/ijms241713372
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Yr Genes in Xinjiang Wheat Cultivars Using Different Molecular Markers

Minghao Zhang,
Ainisai Saimi,
Qi Liu
et al.

Abstract: Wheat stripe rust is a fungal disease caused by Puccinia striiformis f. sp. Tritici (Pst). It significantly impacts wheat yields in Xinjiang, China. Breeding and promoting disease-resistant cultivars carrying disease-resistance genes remains the most cost-effective strategy with which to control the disease. In this study, 17 molecular markers were used to identify Yr5, Yr9, Yr10, Yr15, Yr17, Yr18, Yr26, Yr41, Yr44, and Yr50 in 82 wheat cultivars from Xinjiang. According to the differences in SNP loci, the KAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The highly virulent race CYR34 has overcome resistance previously conveyed by Yr26 ( Han et al., 2010 ). Based on a previous study of wheat in Xinjiang, the frequency of Yr5 is approximately 100% in spring and winter wheat, and that of Yr26 is 84.15% ( Zhang et al., 2023 ). This is in contrast to our results, where we did not identify Yr5 in either wheat population, and similarly no Yr26 gene in spring wheat and only one Yr26 gene in a winter wheat line (2014-132-7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highly virulent race CYR34 has overcome resistance previously conveyed by Yr26 ( Han et al., 2010 ). Based on a previous study of wheat in Xinjiang, the frequency of Yr5 is approximately 100% in spring and winter wheat, and that of Yr26 is 84.15% ( Zhang et al., 2023 ). This is in contrast to our results, where we did not identify Yr5 in either wheat population, and similarly no Yr26 gene in spring wheat and only one Yr26 gene in a winter wheat line (2014-132-7).…”
Section: Discussionmentioning
confidence: 99%
“…With the source variation of stripe rust and the emergence of new virulence factors, many single resistance genes have been overcome. In a previous analysis of wheat resistance genes, polymerization or stacking of multiple genes has been shown to effectively improve resistance ( Zhang et al., 2023 ). In this study, we found that most of the wheat varieties in Xinjiang contained two or more Yr genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the screening of endophytic bacteria of different winter wheat varieties in Xinjiang and the use of strains with significant biocontrol potential to control wheat stripe rust have not been reported. At present, the main research on wheat stripe rust in Xinjiang focuses on physiological species identification [23,24], over-summering regions [25], resistance gene detection [26], deep learning recognition of disease [27], hyperspectral remote sensing [28][29][30], population genetic structures [31], and the minimum detection limit [32].…”
Section: Introductionmentioning
confidence: 99%